Peningkatan kemampuan komunikasi matematis siswa SMP kelas VIII melalui pendekatan open ended - Mudzia Hutama; Widaningsih Pitriyani (IKIP Siliwangi, 2023)
This study aims to examine the achievement, improvement, implementation, and difficulty of mathematical communication skills and the achievement of learning interests of junior high school students through learning using an Open-Ended approach. The method in this study was an experimental method with two class groups, namely the experimental class and the control class; the research design was in the form of pretests, posters, and normalized gain tests. The research test instrument consists of 5 questions on mathematical communication skills in the form of descriptions and questionnaires of student learning interests. The research data were obtained from the results of pretests, posttests, and normalized gain tests, which were processed through normality tests, mann-whitney tests using IBM SPSS 23 software, as well as postes tests for student learning interests processed through normality tests, and homogeneity tests, t-tests using IBM SPSS 23 software. The research data showed that the experimental group's mathematical communication skills increased, while the control class did not.